2014
DOI: 10.1002/cncr.29066
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for advanced‐stage human immunodeficiency virus‐associated classical Hodgkin lymphoma treated with doxorubicin, bleomycin, vinblastine, and dacarbazine plus combined antiretroviral therapy: A multi‐institutional retrospective study

Abstract: ; for the HIV-Associated Hodgkin Lymphoma in the cART Era Study Group BACKGROUND: The treatment and outcomes of patients with human immunodeficiency virus (HIV)-associated Hodgkin lymphoma (HL) continue to evolve. The International Prognostic Score (IPS) is used to predict the survival of patients with advanced-stage HL, but it has not been validated in patients with HIV infection. METHODS: This was a multi-institutional, retrospective study of 229 patients with HIV-associated, advanced-stage, classical HL who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
2
26
2
Order By: Relevance
“…The majority (72.34%) of the patients included in the study had never received ART prior to their lymphoma treatment. This finding is in contrast to European studies in which the majority of patients are ART-exposed [ 12 – 17 ]. The fact that all patients who received ART before the diagnosis of NHL came from the capital could imply that people living in remote rural areas are less likely to receive ART.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The majority (72.34%) of the patients included in the study had never received ART prior to their lymphoma treatment. This finding is in contrast to European studies in which the majority of patients are ART-exposed [ 12 – 17 ]. The fact that all patients who received ART before the diagnosis of NHL came from the capital could imply that people living in remote rural areas are less likely to receive ART.…”
Section: Discussioncontrasting
confidence: 94%
“…Five-year survival in HIV-infected patients diagnosed with systemic NHL was low compared to European cohort studies [ 12 , 18 ], but similar to other Latin American studies [ 19 , 20 ]. Although the difference in survival between NHL patients with and without HIV is generally felt to be improving, we see that the OS in developing countries like Peru continues to lag [ 10 , 19 ].…”
Section: Discussionsupporting
confidence: 80%
“…Considering the dramatic health threats by sexually transmitted co-infections posing to people living with HIV/AIDS in recent years, the current study suggested surveillance drug resistance mutations (SDRMs) as a national surveillance system which was largely consistent with our suggestion[ 24 ]. Other studies further emphasize the association between TDR and HIV subtype among HIV infected MSM, which may be meaningful for STI control[ 25 ],[ 26 ],[ 27 ],[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…With appropriate supportive care, standard regimens such as ABVD or BEACOPP can be delivered. [3942] The results of the largest studies are shown in Table 4 [40,4245]. Greater than normal toxicity must be anticipated and can be partially mitigated by use of G-CSF and sometimes erythropoietin for drug-induced anemia.…”
Section: Treatment Of Hodgkin Lymphoma Patients With Coincident Himentioning
confidence: 99%
“…In a recent large multi-institutional, retrospective study of 229 patients with HIV-associated, advanced-stage, classical HL, patients received ABVD plus combination antiretroviral therapy [46]. Five-year PFS and overall survival rates were 69% and 78%, respectively.…”
Section: Treatment Of Hodgkin Lymphoma Patients With Coincident Himentioning
confidence: 99%